John Locke and the Limits of Religious Liberty: Marriage License Refusal, Religious Freedom Laws, Vaccine Refusal, Contraception Mandate Exemptions, and Ultrasound Requirements. Issue 3 (3rd July 2018) - Reed, Ryan
ABSTRACT: Nearly two hundred fifty years into its existence, the American polity faces a conundrum over a core founding principle: religious liberty. Multiple debates have emerged over the extent and limits of religious liberty, including arguments over how far any one person's religious liberty extends into the public sphere as well as into the private lives of other citizens. Highly influential on James Madison's crafting of the First Amendment, John Locke's Letter Concerning Toleration outlines a strong conception of both religious toleration and of religious liberty. In the "Letter, " Locke's reasoning is sympathetic to the concerns and convictions of believers while remaining cognizant of the calamities to which religious differences can give rise. Further, he provides a robust explication of the mutually exclusive domains of ecclesiastical and civil authorities, now known more colloquially as the division of church and state. In the following article, I illustrate how the principles put forth by Locke offer guidance in adjudicating religious liberty claims in the cases of Kim Davis, religious freedom laws, vaccine refusal, contraception mandate exemptions, and ultrasound requirements.